Evaluation of factors influencing GIFT and comparison of GIFT and IVF results at infertility center of Shariati hospital during 1376-78 - A Alyasin; M Agha Hossinei; A Khademi; H Saeidi Saeidabady (JRI, 2000)
Today there are a number of methods of Assisted Reproductive Technology. The classic method of IVF has a pregnancy rate of 11-12%. GIFT is a new method with a pregnancy rate of 25–35%. In this study 71 patients were included in GIFT cycle. In our study Pregnancy rate of GIFT was 29.6% whereas in 130 cycles of IVF the pregnancy rate was 14.6%. In this study we found that female age, the number of transfered oocytes, serum estradiol on hCG injection day and sperm characteristics were influential factors affecting the outcome of GIFT.
Keywords: GIFT, IVF, Female age, Estradiol, Oocyte